Evidence of multi-stage faulting by clay mineral analysis: Example in a normal fault zone affecting arkosic sandstones (Annot sandstones). (June 2015) - Buatier, Martine D.; Cavailhes, Thibault; Charpentier, Delphine; Lerat, Jérémy; Sizun, Jean Pierre; Labaume, Pierre; Gout, Claude
Abstract: Fault affecting silicoclastic sediments are commonly enriched in clay minerals. Clays are sensitive to fluid–rock interactions and deformation mechanisms; in this paper, they are used as proxy for fault activity and behavior. The present study focuses on clay mineral assemblages from the Point Vert normal fault zone located in the Annot sandstones, a Priabonian-Rupelian turbidite succession of the Alpine foredeep in SE France. In this area, the Annot sandstones were buried around 6–8 km below the front of Alpine nappes soon after their deposition and exhumed during the middle-late Miocene. The fault affects arkosic sandstone beds alternating with pelitic layers, and displays throw of about thirty meters. The fault core zone comprises intensely foliated sandstones bounding a corridor of gouge about 20 cm thick. The foliated sandstones display clay concentration along S–C structures characterized by dissolution of K-feldspar and their replacement by mica, associated with quartz pressure solution, intense microfracturation and quartz vein precipitation. The gouge is formed by a clayey matrix containing fragments of foliated sandstones and pelites. However, a detailed petrographical investigation suggests complex polyphase deformation processes. Optical and SEM observations show that the clay minerals fraction of all studied rocks (pelites and sandstones from the damage and core zones of the fault) is dominated by white micas and chlorite. These minerals have two different origins: detrital and newly-formed. Detrital micas are identified by their larger shape and their chemical composition with a lower Fe–Mg content than the newly-formed white micas. In the foliated sandstones, newly-formed white micas are concentrated along S–C structures or replace K-feldspar. Both types of newly formed micas display the same chemical composition confirmed microstructural observations suggesting that they formed in the same conditions. They have the following structural formulas: Na0.05 K0.86 (Al1.77 Fe0.08 Mg0.15 ) (Si3.22 Al0.78 ) O10 (OH)2. They are enriched in Fe and Mg compared to the detrital micas. Newly-formed chlorites are associated with micas along the shear planes. According to microprobe analyses, they present the following structural formula: (Al1, 48 Fe2, 50 Mg1, 84 ) (Si2, 82 Al1, 18 ) O10 (OH)8 . All these data suggest that these clay minerals are synkinematic and registered the fault activity. In the gouge samples, illite and chlorite are the major clay minerals; smectite is locally present in some samples. In the foliated sandstones, Kubler Index (KI) ((001) XRD peak width at half height) data and thermodynamic calculations from synkinematic chlorite chemistry suggest that the main fault deformation occurred under temperatures around 220 °C (diagenesis to anchizone boundary). KI measured on pelites and sandstones from the hanging and footwall, display similar values coherent with the maximal burial temperature of the Annot sandstones in this area. The gouge samples have a higher KI index, which could be explained by a reactivation of the fault at lower temperatures during the exhumation of the Annot sandstones formation. Highlights: We analysed clay minerals in sandstone, pelite and gouge from the Point Vert fault. Newly formed synkinematic mica and chlorite registrated fault activity and fluid–rock interactions at 220 °C. Kubler Index on mica-illite from foliated sandstones and gouges from the fault core suggest polyphase deformation processes. Microtextural organisation and illite crystallinity in gouge samples fluid–rock interactions at low temperature.